Exploring the Recovery Potential of Critical and Strategic Raw Materials from Traversella Mine (Piedmont, Italy) Waste: A Comparison of Laboratory-Scale Separation Techniques - Gabriele Baldassarre; Camila Mori De Oliveira; Adriano Fiorucci; Rossana Bellopede; Paola Marini (Mining)
The growing demand for green and, therefore, sustainable technologies present new challenges for our society. The European Union (EU) identified the critical raw materials (CRMs) and strategic raw materials (SRMs) necessary for these technologies and introduced policies to reduce reliance on external suppliers, which includes investigating the recovery of CRMs from extractive waste. This study assesses the recovery potential of mine waste collected in the Traversella mine district (Piedmont, Italy), known for its polymetallic Fe-Cu-W deposit. The characterization of waste rock samples involved chemical and mineralogical analyses, revealing metallic-bearing minerals such as magnetite and scheelite. Laboratory-scale magnetic and gravity separation tests were carried out and compared. Magnetic separation resulted in a recovery of 75.4% of Fe, 72.3% of Cu, and 83.7% of W, with a weak concentration. Instead, gravity separation produced high-grade Fe (67.6%) and W (1289 ppm) concentrate with lower recovery rates.